Investigating the contribution of peri-domestic transmission to risk of zoonotic malaria infection in humans - Manin, Benny O.; Ferguson, Heather M.; Indra Vythilingam; Fornace, Kim; William, Timothy; Torr, Steve J.; Drakeley, Chris; Chua, Tock Hing (Public Library of Science, 2016)
Background: In recent years, the primate malaria Plasmodium knowlesi has emerged in human populations throughout South East Asia, with the largest hotspot being in Sabah, Malaysian Borneo. Control efforts are hindered by limited knowledge of where and when people get exposed to mosquito vectors. It is assumed that exposure occurs primarily when people are working in forest areas, but the role of other potential exposure routes (including domestic or peri-domestic transmission) has not been thoroughly investigated.